Alpha herpesvirus exocytosis from neuron cell bodies uses constitutive secretory mechanisms, and egress and spread from axons is independent of neuronal firing activity. - Anthony E Ambrosini; Kayla M Borg; Nikhil Deshmukh; Michael J Berry; Lynn W Enquist; Ian B Hogue (PLoS Pathogens)
Alpha herpesviruses naturally infect the peripheral nervous system, and can spread to the central nervous system, causing severe debilitating or deadly disease. Because alpha herpesviruses spread along synaptic circuits, and infected neurons exhibit altered electrophysiology and increased spontaneous activity, we hypothesized that alpha herpesviruses use activity-dependent synaptic vesicle-like regulated secretory mechanisms for egress and spread from neurons. Using live-cell fluorescence microscopy, we show that Pseudorabies Virus (PRV) particles use the constitutive Rab6 post-Golgi secretory pathway to exit from the cell body of primary neurons, independent of local calcium signaling. Some PRV particles colocalize with Rab6 in the proximal axon, but we did not detect colocalization/co-transport in the distal axon. Thus, the specific secretory mechanisms used for viral egress from axons remains unclear. To address the role of neuronal activity more generally, we used a compartmentalized neuron culture system to measure the egress and spread of PRV from axons, and pharmacological and optogenetics approaches to modulate neuronal activity. Using tetrodotoxin to silence neuronal activity, we observed no inhibition, and using potassium chloride or optogenetics to elevate neuronal activity, we also show no increase in virus spread from axons. We conclude that PRV egress from neurons uses constitutive secretory mechanisms: generally, activity-independent mechanisms in axons, and specifically, the constitutive Rab6 post-Golgi secretory pathway in cell bodies.